2020
DOI: 10.1186/s12986-020-00490-8
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 7 involved in GINSENOSIDE-RB1-mediated anti-obesity via peroxisome proliferator-activated receptor gamma pathway

Abstract: Background: Obesity, characterized by the excessive accumulation of triglycerides in adipocytes and their decreased excretion from adipocytes, is closely related to various health problems. Ginsenoside Rb1 (Rb1), the most active component of the traditional Chinese medicine ginseng, has been reported to have positive effects on lipid metabolism. The aim of the present study was to determine the protective effects of Rb1 on glycolipid metabolism under obesity conditions and its mechanisms and to reveal the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
(55 reference statements)
1
14
0
Order By: Relevance
“…In this study, treatment with ginsenoside Rb1 prevented weight gain and reduced blood glucose and lipid levels in diabetic mice, as reported previously. 18 Importantly, our study clarifies the mechanism of ginsenoside Rb1 in influencing adipocytokine pathways and protecting against diabetic cardiomyopathy. Treatment with ginsenoside Rb1 improved levels of serum IL-1β, TNF-α, MCP-1, IL-6, and CRP, as well as decreased leptin and adiponectin levels.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, treatment with ginsenoside Rb1 prevented weight gain and reduced blood glucose and lipid levels in diabetic mice, as reported previously. 18 Importantly, our study clarifies the mechanism of ginsenoside Rb1 in influencing adipocytokine pathways and protecting against diabetic cardiomyopathy. Treatment with ginsenoside Rb1 improved levels of serum IL-1β, TNF-α, MCP-1, IL-6, and CRP, as well as decreased leptin and adiponectin levels.…”
Section: Discussionmentioning
confidence: 62%
“…For example, ginsenoside Rb 1 has been reported to reduce fasting blood glucose (FBG) levels and triglyceride accumulation and ameliorate insulin and leptin sensitivities. 26 , 27 Ginsenoside Rb 2 could obviously improve glucose metabolism and inhibit gluconeogenesis and hepatic lipid accumulation. 28 , 29 Ginsenoside Re could also decrease FBG levels, food intake, and fasting serum insulin levels and improve glucose tolerance and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have also reported the antidiabetic, anti-obesity and anti-aging effects as well as osteogenesis and angiogenesis effects to alleviate bone disorders. For instance, Zhou et al [ 41 ] have shown that Rb1 could exert protective effect on diabetes by regulating mitochondrial energy metabolism, improving insulin resistance and alleviating the diabetic complications, while Guo et al [ 42 ] demonstrated its anti-obesity activity through the reduction in body weight and improvement in glycolipid metabolism by upregulating proliferator activated receptor gamma (PPARγ) and aquaporin 7 (AQP7) protein levels. More recently, Wu et al [ 43 ] showed that Rb1 could reinforce the osteogenesis differentiation and angiogenesis factor’s expression of bone mesenchymal stem cells.…”
Section: Resultsmentioning
confidence: 99%